Does Bank Corporate Governance Matter for Bank Performance and Risk-Taking? New Insights of an Emerging Economy - Moudud-Ul-Huq, Syed; Zheng, Changjun; Gupta, Anupam Das (Asian Economic and Financial Review, 2018)
This study empirically focuses on the effects of corporate governance on bank performance and risk-taking during the financial crisis of 2007-2008. Using a balanced panel data in an emerging economy, we examine whether banks with corporate governance mechanism have heterogeneous effect on profitability and risk-taking amidst the crisis. Our empirical findings show that corporate governance derives benefits concerning profitability and risk-taking for the banks. Particularly, the key results are as follows: (i) corporate governance is a good mechanism of abating risk during global financial crisis; (ii) a U-shaped negative relation exists between corporate governance, profitability, and risk-taking; (iii) notably, corporate governance in Islamic bank is superior to conventional bank that can increase the stability of efficiency; and (iv) corporate governance has long-run effects on profitability and risk-taking behavior.